Governance and Trust in Family Firms: An Introduction - Eddleston, Kimberly A.; Chrisman, James J.; Steier, Lloyd P.; Chua, Jess H. (Entrepreneurship Theory and Practice, 2010)
We provide an overview of the articles and commentaries devoted to theories of family enterprise in this special issue and link them to the concept of trust. Trust is a governance mechanism and theoretical construct of particular relevance for family firms, encapsulating some of their advantages and disadvantages. Trust is also linked to theoretical frameworks such as agency theory, stewardship theory, social capital theory, and transaction cost economics that are often used in family business studies, including those found in this special issue. Consequently, we advance trust as a bridging concept to reconcile and enhance our understanding of family firms as a unique organizational form.